Sugarcane mosaic virus orchestrates the lactate fermentation pathway to support its successful infection - Jiang, Tong; Du, Kaitong; Wang, Pei; Wang, Xinhai; Zang, Lianyi; Peng, Dezhi; Chen, Xi; Sun, Geng; Zhang, Hao; Fan, Zaifeng; Cao, Zhiyan; Zhou, Tao (Frontiers in Plant Science, 2023)
Viruses often establish their own infection by altering host metabolism. How viruses co-opt plant metabolism to support their successful infection remains an open question. Here, we used untargeted metabolomics to reveal that lactate accumulates immediately before and after robust sugarcane mosaic virus (SCMV) infection. Induction of lactate-involved anaerobic glycolysis is beneficial to SCMV infection. The enzyme activity and transcriptional levels of lactate dehydrogenase (LDH) were up-regulated by SCMV infection, and LDH is essential for robust SCMV infection. Moreover, LDH relocates in viral replicase complexes (VRCs) by interacting with SCMV-encoded 6K2 protein, a key protein responsible for inducing VRCs. Additionally, lactate could promote SCMV infection by suppressing plant defence responses. Taken together, we have revealed a viral strategy to manipulate host metabolism to support replication compartment but also depress the defence response during the process of infection.